2016
DOI: 10.1080/15567249.2011.637546
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of life-cycle assessment ofJatrophabiodiesel

Abstract: This paper provides an analysis of life-cycle assessment (LCA) of Jatropha biodiesel with a view to outline the environmental quality norms of Jatropha biodiesel. The underlying issue is that biofuels need to mitigate the effects of climate change and provide sustainable energy alternatives to fossil fuels. Thus, there is need for empirical evidence on the sustainability of Jatropha biodiesel in order to inform both biofuels policies and development of options for technical intervention to improve the environm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…During peak load condition, the higher levels of smoke emissions were recorded by mineral diesel fuel and Chlorella Emersonii and its fuel blends possess 62.77 HSU (Hartridge Smoke Units) for B40 and 59.8 HSU for B100 which indicated more fuel in the combustion chamber resulting in high un-burned fuels content in exhaust emissions and minimal stoichiometric ratio (table 4). This increased range of smoke emission was attributed to fuel clog, worn, lag in injection pressure and timing, fault in air and fuel filters, deprived fuel mixing rate, minimal adiabatic flame temperature [5,36]. Figure 19 depicts a schematic of combining chlorella emersonii to make biodiesel for testing.…”
Section: Nitrogen Oxide (No X )mentioning
confidence: 99%
See 1 more Smart Citation
“…During peak load condition, the higher levels of smoke emissions were recorded by mineral diesel fuel and Chlorella Emersonii and its fuel blends possess 62.77 HSU (Hartridge Smoke Units) for B40 and 59.8 HSU for B100 which indicated more fuel in the combustion chamber resulting in high un-burned fuels content in exhaust emissions and minimal stoichiometric ratio (table 4). This increased range of smoke emission was attributed to fuel clog, worn, lag in injection pressure and timing, fault in air and fuel filters, deprived fuel mixing rate, minimal adiabatic flame temperature [5,36]. Figure 19 depicts a schematic of combining chlorella emersonii to make biodiesel for testing.…”
Section: Nitrogen Oxide (No X )mentioning
confidence: 99%
“…Studies have discovered many feedstocks for the production of biodiesel that could potentially serve as replacements for fossil fuels [4]. Most commonly used raw biodiesels are soybean oil, mahua seed oil, corn seed oil, jatropha, Pongamia pinnata, and Sunflower oils; biodiesels extracted from these alternative sources have been tested for combustion, tailpipe emissions, and performance and were found effective [5]. Gavhane et al [6] evaluated the influence of silica-based nano additions on the emission performance of soybean-based biodiesel.…”
Section: Introductionmentioning
confidence: 99%
“…To be a suitable alternative of petrodiesel in terms of mitigation of climate change, Jatropha biodiesel needs to be supported by lifecycle data. The environmental benefits of Jatropha biodiesel in comparison to petro-diesel is in doubt [169,170]. Following measures can improve lifecycle performance of Jatropha biodiesel:…”
Section: Lifecycle Assessment (Lca) Of the Jatropha Biofuelmentioning
confidence: 99%
“…There are several LCA studies on the preparation of biodiesel from Jatropha seed, especially from India [27], Malaysia [35], Thailand [36], Mexico [30], Zimbabwe [37], and Indonesia [38], but few studies have been reported from China. Most of the studies chose waste cooking oil (WCO) or palm oil as the feedstock oil, and the evaluation method was only using LCA or Life Cycle Cost (LCC).…”
Section: Introductionmentioning
confidence: 99%